Human Subsistence Strategies and Adaptations in the Lower Yangtze River Region During the Prehistoric Era - Hu, Yaowu (Frontiers in Earth Science, 2021)
Understanding the human subsistence strategies and adaptations in the Lower Yangtze River Region during the prehistoric period is vital to reveal the human-environment interactions, the origin and development of rice agriculture, cultural development, and social complexity. No systematic analysis of isotopic data of human bones in the region has been undertaken within the environmental (sea level), spatiotemporal (site distribution), and economic (animal and plant resources) contexts yet, in order to provide the direct evidence of human diets and trajectory of human subsistence strategies and adaptations. In this paper, we collected the isotopic data in the region as many as possible and incorporated with the environmental, spatiotemporal, and economic information. The results show that humans rarely made use of marine resources when facing the situation of rising sea levels and having good accesses to marine environment during the eastward movement. Alternatively, humans consumed large amount of terrestrial and freshwater or wetland resources. Rice agriculture was still of low-level production and contributed less to human diets. The unique human subsistence strategies enhanced human adaptations to the fluctuation of sea level in the Holocene in eastern China and facilitated the increases of archaeological cultures and human population, challenging the traditional opinion that the developed agriculture is the necessary pathway to develop cultures and grow human population.